Diffuse alveolar haemorrhage: a volatile situation. Issue 1 (4th May 2018) - Lightburn, Thomas; Helliwell, Lee
Summary: We describe the case of a 26‐year‐old patient undergoing a planned procedure who suffered diffuse alveolar haemorrhage (DAH) following exposure to sevoflurane. Although the patient suffers from systemic lupus erythematosus, this was thought to be an unlikely cause of the DAH given the clinical findings, thus the cause was attributed to the volatile agent. This rarely reported phenomenon should be considered in all postoperative cases of pulmonary haemorrhage.